Business success factors within business incubators, validation of the research tool (Factores de éxito empresarial dentro de las incubadoras de empresas, validación de la herramienta de investigación) - Landeros García, Carlos; Terán Cázares, María Mayela; Blanco Jiménez, Mónica (UANL Facultad de Contaduría Pública y Administración, 2021)
The importance that the development of Entrepreneurs in business Incubators has been having has caused this investigation to be carried out. In its first stage, it consists in the theoretical review of the factors that give entrepreneurs a competitive advantage in Business Success such as: Coaching, Business Linking, Digital Social Networks and the Entrepreneur Profile. Therefore, the theoretical justification of these factors and the construction and validation of the instrument are presented. A questionnaire of 51 questions was made and to test its reliability it was applied to 30 study subjects. Using the SPSS, the instrument was validated with Cronbach's alpha factors that show reliable values between .700 and .900 and a final questionnaire was obtained with 46 questions. This work provides a theoretical and methodological contribution to support business success.